ANALYSIS OF CULTURAL INTERACTIONS AMIDST THE RISE OF DIGITAL-BASED ECONOMIC MARKETS IN MEDAN CITY - putri, putri; Astri; Cut; Indah (PERSPEKTIF: Journal of Social and Library Science, 2024)
This research aims to analyze cultural interactions between traders and buyers at the Medan Central Market in facing the rise of digital-based economic markets. Digital transformation and the growth of e-commerce have had a significant impact on trade patterns and consumer behavior, especially in traditional markets. The research method used is a qualitative approach with data collection techniques through in-depth interviews, participant observation and documentation. The research was conducted at the Medan Central Market with research subjects including textile wholesalers and consumers. The research results show that although digitalization has made transactions easier and expanded market reach, many traditional market traders have experienced a decline in income of up to 50% due to reduced customers. However, cultural interactions involving the bargaining process and personal relationships between traders and buyers remain the advantages of traditional markets. On the other hand, the adoption of digital technology by some traders is starting to help increase their competitiveness, although they are still hampered by digital infrastructure and literacy. This research emphasizes the importance of government support in providing digital training and infrastructure, as well as the need for a balanced adaptation strategy to maintain the cultural value of traditional markets in the digital era.